2018
DOI: 10.1039/c8dt01654b
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and structural insights into the nature of the H-cluster precursor on HydF

Abstract: Assembly of an active [FeFe]-hydrogenase requires dedicated maturation enzymes that generate the active-site H-cluster: the radical SAM enzymes HydE and HydG synthesize the unusual non-protein ligands - carbon monoxide, cyanide, and dithiomethylamine - while the GTPase HydF serves as a scaffold for assembly of the 2Fe subcluster containing these ligands. In the current study, enzymatically cluster-loaded HydF ([2Fe]F) is produced by co-expression with HydE and HydG in an Escherichia coli host followed by isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 73 publications
4
15
0
Order By: Relevance
“…More specifically, HydE and HydG are radical SAM enzymes responsible for the construction of a [2Fe] subsite precatalyst on HydF, a scaffold protein that delivers the cofactor to the hydrogenase ( 7 17 ). A combination of FTIR spectroscopy, biochemical assays, biomimetic model chemistry, and DFT calculations has revealed that this precatalyst is strikingly similar to the synthetic [2Fe] subsite mimic [Fe 2 (adt)(CO) 4 (CN) 2 ] 2− ([2Fe] adt ) ( 14 , 18 20 ).…”
mentioning
confidence: 85%
“…More specifically, HydE and HydG are radical SAM enzymes responsible for the construction of a [2Fe] subsite precatalyst on HydF, a scaffold protein that delivers the cofactor to the hydrogenase ( 7 17 ). A combination of FTIR spectroscopy, biochemical assays, biomimetic model chemistry, and DFT calculations has revealed that this precatalyst is strikingly similar to the synthetic [2Fe] subsite mimic [Fe 2 (adt)(CO) 4 (CN) 2 ] 2− ([2Fe] adt ) ( 14 , 18 20 ).…”
mentioning
confidence: 85%
“…In addition to the [4Fe-4S] cluster, there is evidence from EPR spectroscopy that as-isolated and chemically reconstituted HydF can also host a [2Fe-2S] cluster [ 61 , 62 , 63 , 64 , 65 ], which is otherwise lacking in all solved HydF crystal structures [ 48 , 56 ]. Given this discrepancy, it is still unclear whether the presence of a [2Fe-2S] cluster represents a physiological state, a state of partial cluster maturation, or simply arises from an incomplete reconstitution due to the in vitro conditions.…”
Section: The Maturasesmentioning
confidence: 99%
“…In a recent work [ 65 ], the precursor to the [2Fe] H cluster present in HydF (called [2Fe] F cluster) has been suggested to be structurally different from the one present in HydA, based on FT-IR data (see Figure 1 for its structure). [2Fe] F has not been detected by EPR spectroscopy suggesting it is diamagnetic.…”
Section: The Maturasesmentioning
confidence: 99%
“…(adt)(CO) 4 (CN) 2 ] 2− ([2Fe] adt , Fig. 1c) [6,[27][28][29]. Indeed, incorporating the [2Fe] adt complex into either HydF or apo-HydA1 results in semi-synthetic forms of the two proteins, which are spectroscopically and biochemically indistinguishable from the native biological proteins [6,15,28,29,31].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of biomimetic synthetic chemistry, biochemistry, spectroscopy, and quantum chemical calculations has revealed that the pre-catalyst on HydF is strikingly similar, if not identical, to the synthetic complex [Fe 2 I,I (adt)(CO) 4 (CN) 2 ] 2− ([2Fe] adt , Fig. 1 c) [ 6 , 27 29 ]. Indeed, incorporating the [2Fe] adt complex into either HydF or apo-HydA1 results in semi-synthetic forms of the two proteins, which are spectroscopically and biochemically indistinguishable from the native biological proteins [ 6 , 15 , 28 , 29 , 31 ].…”
Section: Introductionmentioning
confidence: 99%